Afghanistan: Organizing Danish civil-military relations - Søren Schmidt (Danish Institute for International Studies (DIIS), 2009)
This report discusses the Danish experience with civil-military integration in the case of Afghanistan. It places emphasis on the political nature of the challenge in high-conflict areas. It finds that fragile, post-conflict situations such as that found in Badahkshan in Afghanistan should be treated differently from the in-conflict, failed state situation as found in Helmand. Where military and civilian activities are to be integrated in failed state situations, the two activities are said to benefit from being organized separately in fragile situations.
Keywords: 300; Friedenssicherung; Internationale Truppe; Katastrophenhilfe; Dänemark; Afghanistan